Shaking table experimental study on pounding between adjacent structures founded on different soil types. (October 2022) - Miari, Mahmoud; Jankowski, Robert
Abstract: The aim of this study is to extensively investigate the effect of the soil type on the response of colliding structures based on shaking table experimental tests. Two single-storey models of steel buildings with different dynamic parameters were considered in this study. Three pounding scenarios were taken into account by applying different seismic gaps (0.5 cm, 1 cm and 1.5 cm as well as the no pounding case). First, the effect of pounding on the response of these two structures was analysed. Then, the effect of the seismic gap on the response of colliding structures was studied. Finally, the effect of soil type on the response of structures exposed to interactions was investigated. Five soil types were considered in the study, which are the five soil types defined in the ASCE 7-10 code (hard rock, rock, very dense soil and soft rock, stiff soil and soft clay soil). The results of the investigation show that pounding significantly increases the level of accelerations of structures during the whole time of vibrations as well as the peak acceleration itself. Pounding is more significant for the flexible structure than for the stiff one. Also, the seismic gap has a significant effect on the acceleration response of colliding structures. Not necessarily larger gap leads to lower responses unless it is large enough to eliminate collisions at all. Moreover, the results of the study show that the soil type has a significant effect on the response of colliding structures. The soil type effect is more significant when pounding takes place. The maximum and minimum peak acceleration differs for various soil types, pounding scenarios, seismic gaps and earthquakes.